1996
DOI: 10.1007/bf03349846
|View full text |Cite
|
Sign up to set email alerts
|

Inositolphosphoglycans are possible mediators of the glucagon-like peptide 1 (7–36)amide action in the liver

Abstract: A potent glycogenic effect for GLP-1(7-36)amide has been found in rat hepatocytes and skeletal muscle, and the specific receptors detected for GLP-1(7-36)amide in these tissue membranes do not seem to be associated to adenylate cyclase. On the other hand, inositolphosphoglycan molecules (IPGs) have been implicated as second messengers in the action of insulin. In a human hepatoma cell line (HEP G-2), we have observed the presence of [125I]GLP-1(7-36)amide specific binding, and a stimulatory effect of the pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…However, several studies have shown that in the liver and skeletal muscle, GLP-1 seems to act through specific receptors, different in structure and signaling pathways from those in the pancreas, which are cAMP associated. Second messengers such as inositol phosphoglycan or phosphatidylinositol 3-phosphate have been proposed (18,23,28,40). In a more recent study (1), activation of phosphatidylinositol 3Ј-kinase, protein kinase B, and mitogen-activated protein kinases has been shown to be involved in the action of GLP-1 upon glycogen synthase a activity in rat skeletal muscle.…”
Section: Discussionmentioning
confidence: 97%
“…However, several studies have shown that in the liver and skeletal muscle, GLP-1 seems to act through specific receptors, different in structure and signaling pathways from those in the pancreas, which are cAMP associated. Second messengers such as inositol phosphoglycan or phosphatidylinositol 3-phosphate have been proposed (18,23,28,40). In a more recent study (1), activation of phosphatidylinositol 3Ј-kinase, protein kinase B, and mitogen-activated protein kinases has been shown to be involved in the action of GLP-1 upon glycogen synthase a activity in rat skeletal muscle.…”
Section: Discussionmentioning
confidence: 97%
“…Further, two groups have reported that GLP-1 has insulin-like activity and stimulates glycogen formation (59) and inhibits glycogenolysis (27) in isolated hepatocytes. These investigators suggest that GLP-1 action in the liver is mediated by receptors that are different in structure and signaling pathways (20,26,27,32,38,56,59). It is also possible that Ex-4 is mediating its actions in the IUGR neonate through GLP-1 receptors in the portal vein, as a number of investigators have shown that Ex-4 can reduce glucose, independent of islet hormones or gastric emptying (3,4,9,28,38,39,41,57).…”
Section: Discussionmentioning
confidence: 99%
“…Thus GLP-1 has been reported to bind to rat hepatic membranes but without influencing adenylate cyclase activity, as expected from the classical GLP-1 receptor (308). Rather, inositol phosphoglycans were thought to act as mediators (291). The same group also described activation of phosphatidylinositol 3-kinase/protein kinase B, protein kinase C, and protein phosphatase-1 pathways to transmit the actions on glycogen synthase in rat hepatocytes (250).…”
Section: Whole Body Effects Peripheral Effects and Effects On Inmentioning
confidence: 99%